THE INFLUENCE OF NUMBER POCKET MEDIA ON THINKING CRITICAL MATHEMATICS OF STUDENTS OF GRADE I ELEMENTARY SCHOOL - Aulia Putri, Naya; Fariha, Balqis; Khalisha, Yasmine; Hasibuan, Mazdalifah; Sari Sitepu, Melyani (Journal of Authentic Research on Mathematics Education (JARME), 2025)
This study aimed to determine the effect of the “number pouch” media on the mathematical critical thinking skills of first-grade students at SD Muhammadiyah 12 Medan. The research population comprised all first-grade students, with one class designated as the experimental group and another as the control group. This quantitative research employed a Pre-Test Post-Test Control Group Design. The sample consisted of 40 students, divided into two classes: 22 students in the experimental group and 18 in the control group. Data analysis was conducted using SPSS 23. The findings indicated that the “number bag” media significantly enhanced students' critical thinking abilities in mathematics, particularly in performing vertical addition operations. The research instrument was a test, and data analysis techniques included validity tests, reliability tests, normality tests, homogeneity tests, N-gain tests, and hypothesis testing. Results from the independent t-test analysis showed a significant value (sig. 2-tailed) of 0.000, which is less than 0.05, leading to the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (H0). This outcome suggests that the “bag of numbers” media positively affects the critical thinking skills of first-grade students at SD Muhammadiyah 12 Medan. Students who received instruction using the “bag of numbers” media achieved higher average scores compared to those who did not use the media, indicating that the independent variable (solution) employed in the study influenced the dependent variable (problem).